Bibliometric analysis of the use of electrospun chitosan nanofibers in biomedical applications - M. Amin, M. Asyraf; Mohd Omar, Suhaila; Kamal Bashah, M. Huzaifilyasir; Mohd Nasir, Mohd Hamzah (University Tun Hussein Onn Malaysia, 2024)
In recent times, the application of electrospun nanofibers derived from chitosan has gained substantial attraction across various biomedical domains. This surge in popularity can be attributed to their unique attributes, which encompass a high surface area-to-volume ratio, customizable pore dimensions, and impressive mechanical characteristics. The objective of this bibliometric investigation is to furnish an overarching view of the realms of application, research advancements, and emerging trends pertaining to electrospun chitosan nanofibers within the biomedical sphere. The data for this study was extracted from Scopus, covering the time span from 2006 to 2023. Following meticulous refinements involving keywords, publication years, research fields, and document types, a total of 243 publications and 1080 authors were included in this analysis. Linear regression computations were conducted, foreseeing the publication of 24 articles in the year 2023. ‘Carbohydrate Polymers’ emerged as the most prominently featured journal with a focus on electrospun chitosan nanofibers for biomedical applications. Iran and China contributed to 27.16% of the publications, with Donghua University as the most prolific institution. Tissue engineering emerged as the foremost domain for the application of electrospun chitosan nanofibers. Furthermore, numerous collaborative efforts and citations among authors, institutions, and countries are anticipated to become more prominent.